Low dietary intake of linoleic acid predisposes to myocardial infarction. Issue 6343 (11th September 1982) - Simpson, H C R; Barker, K; Carter, R D; Cassels, E; Mann, J I
Abstract : Thirty-two men who had recently had a myocardial infarction were matched individually for age with controls who had no evidence of heart disease. The patients had a significantly lower proportion of linoleic acid and a higher proportion of palmitic acid in their plasma triglyceride fatty acids. Analysis of the composition of red-cell membrane phosphatidyl choline, which reflects long-term dietary fat intake, showed a significantly lower proportion of linoleic acid in the patients. These differences suggest that the type of dietary fat consumed might be an important factor in the genesis of ischaemic heart disease.